2020
DOI: 10.1016/j.chaos.2019.109425
|View full text |Cite
|
Sign up to set email alerts
|

Role of vaccine efficacy in the vaccination behavior under myopic update rule on complex networks

Abstract: a b s t r a c tHow to effectively prevent the diffusion of infectious disease has become an intriguing topic in the field of public hygienics. To be noted that, for the non-periodic infectious diseases, many people hope to obtain the vaccine of epidemics in time to be inoculated, rather than at the end of the epidemic. However, the vaccine may fail as a result of invalid storage, transportation and usage, and then vaccinated individuals may become re-susceptible and be infected again during the outbreak. To th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Following Fu et al [59], many recent studies such as Arefin et al [60,61], Huang et al [62], Iwamura & Tanimoto [63], Kabir & Tanimoto [64], and Kabir et al [65,66] used multi-agent-simulation methodology, thus allowing considerable flexibility and realism in the modelling approach, especially in prevention of seasonal influenza where individuals have to revaccinate every year. Furthermore, complex networks provide a platform to model real-world populations [67].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Following Fu et al [59], many recent studies such as Arefin et al [60,61], Huang et al [62], Iwamura & Tanimoto [63], Kabir & Tanimoto [64], and Kabir et al [65,66] used multi-agent-simulation methodology, thus allowing considerable flexibility and realism in the modelling approach, especially in prevention of seasonal influenza where individuals have to revaccinate every year. Furthermore, complex networks provide a platform to model real-world populations [67].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Therefore, a voluntary vaccination model based on game theory has been proposed to explore influences of immunization on the dynamical process in epidemics [13][14][15][16][17][18]. Huang et al [19] proposed a new vaccination update rule: a myopic update rule based on the Fermi function and a new vaccination game. In particular, the utility of risky perception is considered a term of the utility function.…”
Section: Introductionmentioning
confidence: 99%
“…This process needs a contact between them. It is found that the best pattern of contact is contact in the networks [6][7][8][9][10][11], and study epidemic model on networks has been a hot field in mathematical biology [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]35].…”
Section: Introductionmentioning
confidence: 99%